Performance analyses and optimizations of desiccant wheel-assisted atmospheric water harvesting systems based on ideal thermodynamic cycles. (1st October 2021) - Tu, Rang; Liu, Mengdan; Wang, Siqi; Yang, Xu
Highlights: Optimized humidifying systems are provided based on ideal desiccant wheels (DWs). Diagrams are provided to assist selecting optimal heating/cooling temperatures. Highest water harvesting efficiencies the system can achieve are provided. Ambient conditions for the system to be better than direct cooling systems are given. Abstract: This study proposes a novel atmospheric water harvesting system that uses desiccant wheels to transfer vapor from one air stream (Adeh ) to another (Ahum ), and the humidified Ahum is cooled to obtain water. First, the ideal air handling processes of desiccant wheels are introduced, and the heating temperature and ideal humidification efficiency are compared among the three humidification configurations. The system with multi-stage desiccant wheels and independent Adeh performs best, with an ideal humidification efficiency that is 0.4 to 2.2 times higher than that of the other two systems. The ideal water harvesting efficiency of the system is much higher than that of the direct cooling water harvesting method. A two-stage humidification system using actual desiccant wheels is then designed. Driven by ideal heating and cooling systems, water harvesting rates and water harvesting efficiencies are calculated under typical dry and mild working conditions. When the heating temperature is from 40 °C to 90 °C, and the cooling source temperature ranges from 0 °C to 12 °C, diagrams are drawn to assist the selection of the heating temperature and cooling source temperature to obtain the highest water harvesting efficiency for different water harvesting rates. Finally, vapor compression cycles are used as heating and cooling sources, and the performance of the system is compared with that of the direct cooling method. Although this system has higher water harvesting rates, water harvesting efficiencies can be higher when the ambient relative humidity ratio is lower than 60%. With solar thermal energy, water harvesting efficiencies are higher than those of the direct cooling method, especially when the relative humidity ratio is high.